A fiscalização e o processo administrativo nas entidades de previdência privada - Paiva, Mauro Antonio de (2005)
SUMMARY Objective The object of our investigation was to contribute, even though in a very small manner, to the development of the title theme of this paper, specially due to the absence of specialized literature in this field. Justification The theme chosen resulted from verifying that, although Article 202 of our 1988 Constitution refers to a ‘private social security regime’, ‘private’ is significantly mimimized by the extremely strong position Public Powers have in the area. Hypothesis The fact that the inspection and administrative procedures treated here are promoted by the State, markedly reveals the local legislator recognizes that complementary social security, even though rooted in the field of private law, is of relevant public interest, which, by this only, justifies the marked presence of the Administration in every instance of the existence of the entities that explore such activity. Theoretical / Methodological Aspects The survey mainly remained within the group of constitutional principles that regulate Brazilian Social Security. The survey developed is exclusively theoretical; the object of the survey was studied by applying the systematic method. Results In essence, one concludes that the inspection and administrative procedures discussed here – undoubtedly manifestations of the police power the State has in the area – constitute a way through which the Public Powers assure the effectiveness of private social security regulation activity in the country and, by this, achieve the goal of making it faithfully fulfill the very noble role it has within our social security system.